Violation of single-length-scaling dynamics via spin vortices in an isolated spin-1 Bose gas - Schmied, Christian-Marcel; Gasenzer, Thomas; Blakie, P. B. (Physical review. A, Atomic, molecular and optical physics, 2019)
We consider the phase-ordering dynamics of an isolated quasi-two-dimensional spin-1 Bose gas quenched into an easy-plane ferromagnetic phase. Preparing the initial system in an unmagnetized antiferromagnetic state the subsequent ordering involves both polar core and Mermin-Ho spin vortices, with the ratio between the different vortices controllable by the quench parameter. Ferromagnetic domain growth occurs as these vortices annihilate. The distinct dynamics of the two types of vortices means that the domain growth law is determined by two macroscopic length scales, violating the standard dynamic scaling hypothesis. Nevertheless we find that universality of the ordering process manifests in the decay laws for the spin vortices. To provide a fuller picture of the phase ordering dynamics we also present results for the scaling of the order parameter correlation function and the hydrodynamic decomposition of the system kinetic energy.